From dogma to dialogue: Approaches to addressing interreligious intolerance - Styven Bill Chevyn Tambunan; Riris Johanna Siagian (KAMASEAN: Jurnal Teologi Kristen, 2026)
The phenomenon of interreligious intolerance is still a serious challenge in people’s lives, both globally and in Indonesia. Intolerance often arises from a rigid and exclusive interpretation of religious dogma, thus triggering discrimination, conflict, and rejection of groups with different beliefs. This article aims to examine the relationship between dogma and intolerance and explore interreligious dialogue as an alternative approach in building more inclusive religious relations. This research uses qualitative methods with a library research approach and a narrative literature review. Data were obtained from various books, journal articles, and theological works discussing dogma, intolerance, and interreligious dialogue, and were then analyzed descriptively and comparatively by applying source triangulation. The research results show that intolerance is not primarily caused by the existence of dogma, but rather by exclusive interpretations that reject the existence and dignity of other groups. By utilizing Raimon Panikkar’s typology of dialogue, namely dialectical and dialogical dialogue, this article shows that religious beliefs can be maintained while opening up a space for encounters that respect differences. The contribution of this research lies in the application of Panikkar’s dialogue framework in the context of Indonesia’s religious plurality as an effort to encourage a shift from dogmatic exclusivism to dialogical inclusivism.